Manajemen Dan Administrasi Organisasi Rumah Sakit Di Pusat Kesehatan Masyarakat Graha Indah Balikpapan - Suwitno Sanjaya; Sheva Arlinda; Warlinda (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Efforts to enhance service quality are pivotal for elevating the standard of health services. This challenging task extends beyond advanced health facilities like hospitals to all levels of primary health care, including Community Health Centers (Puskesmas). By recognizing the value of effective management and administration, we can devise suitable strategies to boost service quality. The method employed in this study is a qualitative descriptive method with a literature study type. The literature study in this research, a series of activities related to library data collection methods, reading and recording, and managing research data objectively, systematically, analytically, and critically, sheds light on the analysis of competencies and the crucial role of health administrators in enhancing service quality. The findings reveal that the Graha Indah Balikpapan Community Health Center grapples with significant operational challenges in several areas, including correspondence, employee file storage, and immunization polyclinic waiting room facilities. The irregular correspondence decreases work efficiency and increases the risk of document loss. Disorganized employee file storage impacts employee productivity, jeopardizes the loss of crucial information, and disrupts patient care. The inadequate waiting room conditions in the immunization polyclinic also disrupt the service process and compromise patient comfort. The research suggests implementing a digital-based document management system to streamline the search, tracking, and archiving of letters and create clear SOPs (Standard Operating Procedures) for the flow of incoming and outgoing mail.